Competition among non-profit organizations for private donations - Estevão, Carine da Silva (2019)
This Master thesis aims firstly, to evaluate the influence that fundraising expenditures made by a non-profit organization has on its own private donations and on the private donations received by all the other non-profit organizations, in the non-profit market. The relationship between own-fundraising expenditures and own-private donations will be useful in answering a second research question, which aims to discover the objective function of a non-profit organization, which can be a net revenue maximizer or a budget maximizer. The latter attribution is related on the fundraising behaviour of the considered non-profit. Thirdly, this thesis purposes to evaluate the effect government grants have on private donations received by a given non-profit organization and on private donations received by all the other non-profits. Using U.S. non-profit organizations’ yearly tax return data from 2005 to 2010, the answers to the three research issues will be given by the estimation of a demand model, more precisely, by the estimation of a discrete choice demand model, which is the Multinomial Logit (MNL) developed by McFadden (1978, 1981). The empirical findings suggest that fundraising expenditures made by a given non-profit organization affect positively its own private donations and affect the private donations of some other non-profits, not of all of them. Besides, at the aggregate level by grouping non-profits into sectors, the effect of own-fundraising expenditures on own-private donations is positive, however when considering the cross-effect of fundraising expenditures made by one sector on private donations received by other sectors, the effect is zero, thus there is no cross-effect when considering non-profits at the aggregate level. Grounded on the fundraising effect results, this master thesis finds out that that the non-profits considered are neither net revenue maximizer nor budget maximizer organizations. Subsequently, the empirical results indicate that government grants have no effect on private donations, because the parameter that captures the effect is statistically not significant.